THE STRATEGY FOR RISK MANAGEMENT OF TRANSMISSION SYSTEMS OF LAO ELECTRIC ENTERPRISESTHE STRATEGY FOR RISK MANAGEMENT OF TRANSMISSION SYSTEMS OF LAO ELECTRIC ENTERPRISES - Xayphone Dalasene, Heuangsi (Journal of Buddhist Anthropology, 2022)
The objectives of the research article were to: 1) study risk management of transmission systems of Lao electric enterprises, 2) define strategy for risk management of transmission systems of Lao electric enterprises, and 3) evaluate publish strategy about risk management of transmission systems of Lao electric enterprises. This was research and development method by 3 phases, such as the first to study risk management of transmission systems, a sample group of 251 persons who was operator of state electricity enterprises on electricity transmission system duty, the questionnaire was used with statistics on frequency, percentage, mean and standard deviation. The second, to define the strategy for risk management of transmission systems by the key informants were 15 qualified persons, and also using in-depth interviews, group discussions and content analysis, and the third, the evaluation and publish strategy of risk management transmission systems by the key informants were 30 person who are executives in Lao electricity enterprises, for using an assessment by specific selected of the key informants with statistics of frequency, percentage, mean, standard deviation and summarize the overview. This research found that: 1) the risk condition with a moderate level ( = 3.18, S.D. = 0.91) such as 1.1) financial, 1.2) law system, 1.3) strategy, and 1.4) operations. The risk management with a moderate level ( = 3.26, S.D. = 0.99) such as 1.1) search and identify, 1.2) analysis, 1.3) strategic, and 1.4) evaluation. 2) The strategic definable consists of vision, mission, goals and strategies including with 2.1) financial management, 2.2) laws management, 2.3) corporate strategy management, and 2.4) operational management And 3) The strategic evaluation was appropriate and possibility, average level >3.51 or higher was considered to pass the assessment criteria. The objectives of the research article were to: 1) study risk management of transmission systems of Lao electric enterprises, 2) define strategy for risk management of transmission systems of Lao electric enterprises, and 3) evaluate publish strategy about risk management of transmission systems of Lao electric enterprises. This was research and development method by 3 phases, such as the first to study risk management of transmission systems, a sample group of 251 persons who was operator of state electricity enterprises on electricity transmission system duty, the questionnaire was used with statistics on frequency, percentage, mean and standard deviation. The second, to define the strategy for risk management of transmission systems by the key informants were 15 qualified persons, and also using in-depth interviews, group discussions and content analysis, and the third, the evaluation and publish strategy of risk management transmission systems by the key informants were 30 person who are executives in Lao electricity enterprises, for using an assessment by specific selected of the key informants with statistics of frequency, percentage, mean, standard deviation and summarize the overview. This research found that: 1) the risk condition with a moderate level ( = 3.18, S.D. = 0.91) such as 1.1) financial, 1.2) law system, 1.3) strategy, and 1.4) operations. The risk management with a moderate level ( = 3.26, S.D. = 0.99) such as 1.1) search and identify, 1.2) analysis, 1.3) strategic, and 1.4) evaluation. 2) The strategic definable consists of vision, mission, goals and strategies including with 2.1) financial management, 2.2) laws management, 2.3) corporate strategy management, and 2.4) operational management And 3) The strategic evaluation was appropriate and possibility, average level >3.51 or higher was considered to pass the assessment criteria.